SIMULASI NUMERIK PENGARUH VARIASI RASIO PANJANG LEADING EDGE TERHADAP KARAKTERISTIK AERODINAMIKA PADA MOBIL PICK UP - Md Ranasandhya Amy Pratyaksa (Otopro, 2020)
The aerodynamic style influences fuel consumption due to drag and the stability of the vehicle speed due to the force lift. Varying the geometry of the leading edge is estimated to have an effect on aerodynamics. This study uses a car pickup model with dimensions like the actual size. Geometry Leading Edge can be modified so that in the variation of the ratio of length leading edge of the vehicle's overall length ( ): ; and . The research method used is a 2-D numerical simulation underconditions steady and unsteady using software ANSYS FLUENT 2019 R3. The mesh using Hybrid model, its triangular and rectangular shape. The viscous model used by k-epsilon Realizable with variation Reynolds Number 7.15 x 104; 2.6 x 106; 3.26 x 106 and 3.91 x 106. The result data analyzed are coefficient lift (CL), coefficient drag (CD), velocity contour, velocity streamline, and pressure contour. From the simulation results, varying ratio of the length of leading edge can affect aerodynamic characteristics of the car. The greater leading edge ratio can delay separation above the car. In addition, the momentum deficit behind the vehicle is also getting smaller. Variation of the length ratio of leading edge is the best variation, having a coefficient drag (CD) of 0.72 with a percentage decrease of 4% and a coefficient lift (CL) of 0.07 with a reduction percentage of 36.36% of the standard variation. CD and CL values go down making fuel consumption more efficient and the car more stable.